STUDY OF THE IMPACT OF INNOVATIVE TECHNOLOGIES ON MECHANICAL ENGINEERING, TRANSPORT AND AGRICULTURE - Mukhammadbobir Khusanboyev (American Journals Publishing, 2023)
This scientific article explores the transformative influence of innovative technologies on the fields of mechanical engineering, transport, and agriculture. The study delves into the recent advancements that have reshaped these industries, emphasizing the positive outcomes and potential challenges. Through a systematic analysis, the article aims to provide valuable insights for researchers, practitioners, and policymakers navigating the dynamic landscape of technological integration in these crucial sectors.
Keywords: Innovative Technologies, Mechanical Engineering, Transport, Agriculture, Automation, Artificial Intelligence, Sustainable Practices, Precision Agriculture, Smart Transportation, Industry 4.0.